Entropy generation analysis of mhd micropolar nanofluid flow over a moved and permeable vertical plate - Mesbah, Abderaouf; Allouaoui, Reda; Bouazis, Amina Manal; Bouazis, Mohamed Najib (Zielona Góra: Uniwersytet Zielonogórski)
The goal of this paper is to learn more about how a magnetic field, Brownian motion, and thermophoresis diffusion influence convective heat transfer in a micropolar-nanofluid flow's laminar boundary layer. Near a vertically moving, permeable plate, the complex fluid is subjected to MHD.
Keywords: entropy analysis; magnetohydrodynamics; micropolar-nanofluid; micro-rotation; moved plate